A computer package for simulation and analysis of rotary forging - Mansour, Saeed (1988)
This thesis presents the development of a software package to simulate and graphically represent the tool/workpiece kinematics in rotary forging. A hypothetical workpiece of non-constant volume is always used. Share changes are achieved by a process of material removal, analogous to metal cutting. Using a quantitative approach, the software is shown to be capable of calculating the tool/workpiece instantaneous contact zone and the volume of material being removed. The software has been developed and used to produce an analysis of radially configurated conic tools. This is believed to be a unique approach to the simulation of the rotary forging process.